Critical Rationalism, the Social Sciences and the Humanities
XVIII, 288 p.
Keywords: An outstanding feature of this book is the broad range of the contributors, drawn from Europe, the Middle East and North America, testifying both to the range of Professor Agassi's interests and the geographical spread of his influence. Most contributors use Agassi's ideas as a springboard to engage in debate on issues, or offer a contribution in an area that interests him. In this volume contributors consider such questions as Agassi's philosophy of education, in practice as well as in theory; the impact of psychologism in philosophy; the origins of critical rationalism in the Bible; the debates in economics stimulated by the work of Popper and Agassi, and many other topics. Besides the special topics, the reader gains some sense of the fruitfulness of critical rationalism in the hands of Agassi's friends and colleagues.